Final answer:
To simplify the expression -0.6a^2b * (-10ab^2), we multiply the coefficients (-0.6 and -10) and combine the variables (a^2 * a = a^3 and b * b^2 = b^3). The simplified expression is 6a^3b^3.
Step-by-step explanation:
In this question, we have the expression -0.6a^2b * (-10ab^2). To simplify this expression, we multiply the coefficients (-0.6 and -10) and combine the variables (a^2 * a = a^3 and b * b^2 = b^3). The result is -0.6 * -10 * a^3 * b^3, which simplifies further to 6a^3b^3.